Nonprofessional Healthcare Staff Perceptions Regarding Inmate Self-Injury in Georgia - Harmer, Alisa Adele (2018)
Self-injury in correctional facilities is an increasing problem. Healthcare staff are tasked with responding to and treating self-injurious inmates. Research concerning the perceptions of prison self-injury depended on the experiences of professional healthcare staff and showed that specialized training reduced anxiety and altered perceptions. The perceptions of nonprofessional healthcare staff regarding inmate self-injury have not been studied. The purpose of this research was to understand the perceptions of inmate self-injury maintained by untrained healthcare staff through evaluation of their expressed experiences with self-injuring inmates. The research was based on the humanistic nursing theory. A phenomenological approach guided interviews of 8 healthcare staff having direct contact with inmates who self-injure. Participants had a past or present employment status with a State of Georgia Department of Corrections North Region correctional facility. Data were reviewed and coded to best reflect what it means to be a nonprofessionally trained healthcare member responding to inmate self-injury. Nonprofessional healthcare staff perceived that various experiences affected their level of ease and certainty, they operated as preservers of life and active listeners, felt that other healthcare staff held negative opinions, and were very helpful and supporting. Staff perceived that challenges prevented their success in managing self-injury. Last, nonprofessional staff perceived themselves as very helpful and therapeutic. This study promotes social change by encouraging staff to share knowledge, experience, and practical help with each other while building cohesive and collaborative relationships